Capital and Labor in Thomas Pynchon's Novel Against the Day - Grgas-Mufa, Stipe (2010)
The author reads Pynchon's novel as staging the conflict between capital and labor. This allows him to ask two more fundamental questions: 1) can Pynchon's novel be read as an allegorical purchase on the contemporary USA, and 2) how does Pynchon work against the proclivity to pass over the problematic of capital in American fiction.
Projekt MZOS
ENG